Baricitinib therapy response in rheumatoid arthritis patients associates to STAT1 phosphorylation in monocytes - Tucci, Gloria; Garufi, Cristina; Pacella, Ilenia; Zagaglioni, Marta; Pinzon Grimaldos, Alessandra; Ceccarelli, Fulvia; Conti, Fabrizio; Spinelli, Francesca Romana; Piconese, Silvia (Frontiers in Immunology, 2022)
Baricitinib is a Janus kinase (JAK) 1 and 2 inhibitor approved for the treatment of rheumatoid arthritis (RA). The JAK/STAT system is essential in the intracellular signaling of different cytokines and in the activation process of the monocyte lineage. The aim of the present study was to verify the effects of baricitinib on STAT phosphorylation on monocytes of RA patients and to evaluate the correlation between STAT phosphorylation and response to therapy. We evaluated patients’ disease activity (DAS28PCR) at baseline (T0) and after 4 and 12 weeks (T1-T3) of treatment with baricitinib, dividing them into responders (n=7) and non-responders (n=7) based on the reduction of DAS28PCR between T0 and T1 of at least 1.2 points. STAT1 phosphorylation was analyzed at T0/T1/T3 in monocytes through flow cytometry, at basal conditions and after IL2, IFNα and IL6 stimulation. We showed that monocyte frequency decreased from T0 to T1 only in responders. Regarding the phosphorylation of STAT1, we observed a tendency of higher basal pSTAT1 in monocytes of non-responder patients and, after 4 weeks, a significant reduction of cytokine-induced pSTAT1 in monocytes of responders compared to non-responders. The single IFNα stimulation only partially recapitulated the differences in STAT1 phosphorylation in the two patient subgroups. Finally, responders showed an increased IFN signature at baseline compared to non-responders. These results may suggest that monocyte frequency and STAT1 phosphorylation in circulating monocytes could represent early markers of response to baricitinib therapy.